Arc/Arg3.1 defines dendritic cells and Langerhans cells with superior migratory ability independent of phenotype and ontogeny in mice. Issue 5 (6th March 2019) - Tintelnot, Joseph; Ufer, Friederike; Engler, Jan Broder; Winkler, Hana; Lücke, Karsten; Mittrücker, Hans‐Willi; Friese, Manuel A.
Abstract: The key function of migratory dendritic cells (migDCs) is to take up antigens in peripheral tissues and migrate to draining lymph nodes (dLN) to initiate immune responses. Recently, we discovered that in the mouse immune system activity‐regulated cytoskeleton associated protein/activity‐regulated gene 3.1 ( Arc/Arg3.1 ) is exclusively expressed by migDCs and is a central driver of fast inflammatory migration. However, the frequency of Arc/Arg3.1‐expressing cells in different migDC subsets and Langerhans cells (LCs), their phylogenetic origin, transcription factor dependency, and functional role remain unclear. Here, we found that Arc/Arg3.1 + migDCs derived from common DC precursors and radio‐resistant LCs. We detected Arc/Arg3.1 + migDCs in varying frequencies within each migDC subset and LCs. Consistently, they showed superiority in inflammatory migration. Arc/Arg3.1 expression was independent of the transcription factors Irf4 or Batf3 in vivo. In intradermal Staphylococcus aureus infection that relies on inflammatory antigen transport, Arc/Arg3.1 deletion reduced T‐cell responses. By contrast, Arc/Arg3.1 deficiency did not hamper the immune response to systemic Listeria monocytogenes infection, which does not require antigen transport. Thus, Arc/Arg3.1 expression is independent of ontogeny and phenotype and although it is restricted to a small fraction within each migDC subset and LCs, Arc/Arg3.1 + migDCs are important to facilitate infectious migration. Abstract : The intracellular protein Arc/Arg3.1 is exclusively expressed by migDCs and marks a subpopulation of Arc/Arg3.1 + migDCs. These migDCs derive from common DC precursors and Langerhans cells and are independent of the transcription factors Irf4 or Batf3. They are superior in inflammatory migration such as in mounting an immune response to intradermal Staphylococcus aureus infection.